2000
DOI: 10.1074/jbc.275.19.14494
|View full text |Cite
|
Sign up to set email alerts
|

The Phosphorylation State and Expression of Soybean BiP Isoforms Are Differentially Regulated following Abiotic Stresses

Abstract: The mammalian BiP is regulated by phosphorylation, and it is generally accepted that its unmodified form constitutes the biologically active species. In fact, the glycosylation inhibitor tunicamycin induces dephosphorylation of mammalian BiP. The stress-induced phosphorylation state of plant BiP has not been examined. Here, we demonstrated that soybean BiP exists in interconvertible phosphorylated and nonphosphorylated forms, and the equilibrium can be shift to either direction in response to different stimuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 43 publications
1
69
0
Order By: Relevance
“…The simplest explanation for these results is that phosphorylation of soybean BiP by osmotic stress may serve as a distinct regulatory function, and because it is not restricted to the oligomeric form of BiP, it may occur at different sites. This argument is supported by the observation that despite its phosphorylation state, the soybean BiP isoform from water-stressed leaves exhibits proteinbinding activity and associates with a water stress-induced 28 kDa polypeptide (Cascardo et al, 2000). Soybean BiP has also been shown to associate detectably with normal storage proteins in vitro .…”
Section: Endoplasmic Reticulum-resident Molecular Chaperonessupporting
confidence: 62%
See 1 more Smart Citation
“…The simplest explanation for these results is that phosphorylation of soybean BiP by osmotic stress may serve as a distinct regulatory function, and because it is not restricted to the oligomeric form of BiP, it may occur at different sites. This argument is supported by the observation that despite its phosphorylation state, the soybean BiP isoform from water-stressed leaves exhibits proteinbinding activity and associates with a water stress-induced 28 kDa polypeptide (Cascardo et al, 2000). Soybean BiP has also been shown to associate detectably with normal storage proteins in vitro .…”
Section: Endoplasmic Reticulum-resident Molecular Chaperonessupporting
confidence: 62%
“…Soybean BiP expression has also been shown to respond to a variety of abiotic and biotic stress conditions, including water stress, fungus infestation, insect attack, nutritional stress, and elicitors of the plant-pathogenesis response (Carolino et al, 2003). Soybean BiP exists in interconvertible phosphorylated and non-phosphorylated forms, and the equilibrium can be shifted to either direction in response to different stimuli (Cascardo et al, 2000). In contrast to tunicamycin treatment, water stress stimulates phosphorylation of BiP species in cultured soybean cells and stressed soybean leaves.…”
Section: Endoplasmic Reticulum-resident Molecular Chaperonesmentioning
confidence: 99%
“…BiP might facilitate proper folding and maturation of a selected group of water stress-induced secretory proteins, which are probably involved in the osmotic response mechanism. In fact, droughtinduced proteins, which are targeted to the secretory pathway, have been identified in a wide range of plant species (Ingram and Bartels, 1996;Riccardi et al, 1998) and BiP has been shown to associate with water-stress induced proteins (Cascardo et al, 2000). Overexpression of BiP may provide an indirect effect in stress tolerance by allowing the cells to control more efficiently the concentration of specific defense proteins before the stress condition has reached its maximum deleterious effect.…”
Section: Discussionmentioning
confidence: 99%
“…A 70 kDa HSP (spot 3) and a putative aldose reductase (spot 7) appeared as two protein spots, and a putative embryo-specific protein (spot 10), one of the LEA proteins, as three spots. In cultured soybean cells, a type of 70 kDa HSP (binding immunoglobulin protein) localized to the endoplasmic reticulum undergoes phosphorylation under water stress (Cascardo et al 2000). In addition, phosphorylated LEA protein is present in mature dry seeds of Arabidopsis (Irar et al 2006).…”
Section: Isoforms Of Stress-related Proteins In Rice Seedsmentioning
confidence: 99%